EVALUASI DAMPAK PEMBANGUNAN PENATAAN BATANG AGAM TERHADAP PEREKONOMIAN MASYARAKAT LOKAL - Amanda Ratu Hamizah; Amanda Febriani Putri; Amelia Indah Sari; Boni Saputra (STKIP Subang, 2026)
Riverbank development is a form of infrastructure intervention that has the potential to change the economic dynamics of surrounding communities. This study aims to evaluate the impact of the Batang Agam development on the local economy in PayakumbuhCity, West Sumatra. The method used was a literature review with a qualitative approach through content analysis techniques of various relevant academic sources. The results indicate that the Batang Agam development has had a positive economic impact in the form of expanded business opportunities, job creation, and increased land and property values in the surrounding area. The development also encourages the growth of Micro, Small, and Medium Enterprises (MSMEs) in the culinary, trade, and service sectors along with increased tourist visits. However, there are also negative impacts that require attention, namely the relocation of residents and businesses from the riverbanks and increased competitive pressures for local businesses with limited capital. This study recommends the need for affirmative action policies from the local government in the form of providing business facilities, entrepreneurship training, and access to capital to ensure the economic benefits of development are distributed fairly and sustainably to the entire community.